2004
DOI: 10.1038/sj.onc.1208252
|View full text |Cite
|
Sign up to set email alerts
|

Ral-GTPases: good chances for a long-lasting fame

Abstract: Oncogenic constitutively active RAS mutants are found in 30% of all human cancers. In addition to acquisition of point mutations, functional activation of RAS may occur as a part of altered intracellular signal transduction associated with oncogenic transformation. Since RAS appears as a common signal transduction crossroad for various regulatory pathways, there is hardly an aspect of malignant phenotype that was not described as being affected by its activation (reviewed in Malumbres and Barbacid, 2003;and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Although little is known about what activates PLD activity in MDA-MB-231 cells, it is of interest that the regulators of PLD1, RalA and Arf6 (8, 29 -31), are both implicated in the regulation of cell migration. RalA was recently reported to stimulate the metastasis of transformed cells (32,33) and was shown previously to activate metalloproteases (34). Other studies also link PLD activity with protease secretion (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…Although little is known about what activates PLD activity in MDA-MB-231 cells, it is of interest that the regulators of PLD1, RalA and Arf6 (8, 29 -31), are both implicated in the regulation of cell migration. RalA was recently reported to stimulate the metastasis of transformed cells (32,33) and was shown previously to activate metalloproteases (34). Other studies also link PLD activity with protease secretion (35)(36)(37).…”
Section: Discussionmentioning
confidence: 99%
“…RalA has been implicated in the regulation of exocytosis, transcription, secretion, cell transformation and tumor progression [reviewed in (Feig, 2003;Feinstein, 2005)]. When we overexpressed HA-tagged-RalA and FLAG-tagged Aβ in 293T cells, we found that immune complexes isolated using either HA-or FLAG-specific antibodies contained both RalA and Aβ ( Figure 3E).…”
Section: The Small Gtpase Rala Interacts With Pp2a Aβmentioning
confidence: 95%
“…The RalA dephosphorylation resulted in dramatic decrease of RalA activity as detected by its ability to bind the RalBP-1 effector protein [83]. The RalA GTPase is implicated in regulation of several signaling pathways relevant to transformation (reviewed in [92][93][94]). Pathways reported to be regulated by RalA include the activation of phospholipase D1 and Src kinase [95,96], vesicle transport [97], increased cell motility [98][99][100][101] and anchorage-independent growth [102][103][104].…”
Section: The Role Of Pp2a Aβ In Tumor Suppressionmentioning
confidence: 99%